“The New Normalcy” as the Art of the Possible: Alternating Economic Strategies under Xi Jinping - M. V. Karpov (Сравнительная политика, 2021)
The period of Xi Jinping’s rule in the sphere of economic policy is characterized by a sequential alternation of essentially different macroeconomic strategies, united by the general term “new normal”. To date, none of these strategies have met with fundamental success.